Limit and Creation. Towards an Ethic of Self-Limitation in the Digital Era - De Cesaris, Alessandro (ETHICS IN PROGRESS, 2017)
Aim of this article is to analyse the relationship between creativity, freedom and future in contemporary society. The main focus is on the notion of creativity in our digital era. Common sense understands creativity as a concept implying something new, something original that did not exist before. And yet in our society the constant overflow of news, products and contents doesn’t surprise anymore, is no longer connected to a truly creative act. The complete lack of limits seems to be our society’s own limit, since newness is not experienced anymore as something really new. The solution to this situation is a new ethic of self-limitation that reshapes our idea of creativity and bases it on different criteria. The first part of the article is an analysis of hypermodern society. Hypermodernity is defined through three features: quantity as a qualitative element, override of distance, sublation of perspective. Unlike postmodern society, hypermodernity defines itself positively on the basis of some technological and social results that are experienced as improvements. In the second part of the article the paradox of hypermodern society is discussed: despite its obsession for newness, despite the huge spread of creative jobs and the passion for future, newness seems to be something given an usual, being creative means conforming to given standards, and future is almost completely implemented into present. In the last part of the article I argue that a solution to this situation is an ethic of selflimitation, in which a rediscovery of limit leads to a new concept of creativity no longer based on quantitative increment, but rather on the ideas of qualitative selection, objective distance, personal perspective. According to this view, being creative is no longer a matter of content, but rather of form. I will also argue that the aesthetics of Oulipo, a French literary movement of the Sixties, already expressed this stance in a very similar situation.